Moving Up the Ladder? The Impact of Migration Experience on Occupational Mobility in Albania - Carletto, Calogero (2012)
This study uses the 2005 Albanian Living Standards Measurement Study Survey and estimates the impact of international migration experience on the occupational mobility of return migrants vis-a-vis working-age Albanian residents that never migrated. Controlling for the non-random nature of international migration and return, the results show that past migration experience increases the likelihood of upward occupational mobility. Since such impact is likely to depend on differences in earning potentials and opportunities for skill acquisition across destination countries, we explore the heterogeneity of impact by host country. The results indicate that the positive effect of past migration experience on upward occupational mobility is driven by past migration experience in Italy and countries further afield, while past migration experience in Greece does not exert any significant impact on mobility outcomes.